Engaging Employees for the Non-Profit Organization - Iskandar, Krista Daisy (Journal of Business and Management, 2012)
Recognizing the engagement levels of employees is still a grey area that organizations are less aware of. Employee engagement actually creates many improvements within the organization that can result in employee work productivity hence increasing the organization capability.Employee engagement mapping is a holistic tool of seek what variables are meaningful and satisfactory to the employee that increase not only the work motivation and commitment, but further than that which is to perform and strive organization goals regardless of work expectation. This paper elaborates the employee engagement variables and its influential variable items which affect engagement. The writer shares 108 questionnaires as primary data in which respondents are employees of a certain non-profit organization. Moreover, we use the meaningful work-job satisfaction quadrant, to analyze all the information. From this research, it is offered a framework to develop strategies in human resource management that fosters engagement. Keywords: employee engagement, performance management, job satisfaction, meaningful work, human capital management